Indonesian Language Learning Motivation To Support The National Literacy Movement To Make It More Fun For Students Of Smp Negeri 02 Kota Bengkulu - Fitria, Yenni; Lestari , Titje Puji; Diana, Eli; Juwita; Dina, Tri; Luthfia, Izza (Universitas Dehasen Bengkulu, 2019)
Socialization in building enthusiasm and motivating students in participating in Indonesian language learning at SMP Negeri 2 Bengkulu City. This activity was carried out on January 14 2020 at SMP Negeri 2 Bengkulu City. The number of participants who took part in the counseling was around 30 people. This activity aims to increase the enthusiasm of students in participating in learning Indonesian which they have considered boring so far. So that with the existence of motivation and sharing experiences in learning problems faced by students, a pleasant learning of Indonesian will be established for students in the future. From the results of community service activities it was found that the inhibiting factors for students' motivation in learning Indonesian at school varied from laziness that arose from the students themselves, Indonesian language lessons which were placed during the day so as to make students easily sleepy, ways of learning or delivering material from monotonous teacher so it is not interesting. From the results of that discussion, it can be concluded that the ability of each child is different in capturing Indonesian language material. The enthusiasm that exists in students can increase if other factors support it. So as a party you should pay attention to other supporting factors that are going well when learning Indonesian at SMP N 2 Bengkulu City and can increase student creativity in writing.